2013
DOI: 10.1093/carcin/bgt176
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of serum sarcosine and risk of prostate cancer in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial

Abstract: Metabolomic profiling has identified, sarcosine, a derivative of the amino acid glycine, as an important metabolite involved in the etiology or natural history of prostate cancer. We examined the association between serum sarcosine levels and risk of prostate cancer in 1122 cases (813 non-aggressive and 309 aggressive) and 1112 controls in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial. Sarcosine was quantified using high-throughput liquid chromatography-mass spectrometry. A significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
3
30
2
Order By: Relevance
“…As opposed to the findings from a recent Swedish Mendelian randomization study (7 ), we did not observe significant associations between plasma dimethylglycine and incident T2D. Also, there was no overall relationship between serum sarcosine and incident T2D; however, lower serum sarcosine was observed among patients with established T2D both in the current study and in a survey among US men (25 ).…”
Section: Discussioncontrasting
confidence: 99%
“…As opposed to the findings from a recent Swedish Mendelian randomization study (7 ), we did not observe significant associations between plasma dimethylglycine and incident T2D. Also, there was no overall relationship between serum sarcosine and incident T2D; however, lower serum sarcosine was observed among patients with established T2D both in the current study and in a survey among US men (25 ).…”
Section: Discussioncontrasting
confidence: 99%
“…However, high levels of sarcosine were associated with nonaggressive PrCa cases with an OR of 1.44. The association between sarcosine levels and PrCa diagnosis was stronger in men with diabetes and among smokers [110].…”
Section: Sarcosinementioning
confidence: 84%
“…Many studies led to interest in sarcosine as a prostate cancer biomarker but in many of such studies, results have been conflicting; some indicated higher risk associated with higher levels of sarcosine and others, a lower risk 9,10 . In order to definitively assess the potential of serum sarcosine for further study, we are reporting a preliminary data for its reference value in our locality.…”
Section: Discussionmentioning
confidence: 99%